Probing Relevant Molecules in Modulating the Neurite Outgrowth of Hippocampal Neurons on Substrates of Different Stiffness - Chen, Wei-Hsin; Cheng, Sin-Jhong; Tzen, Jason T. C.; Cheng, Chao-Min; Lin, Yi-Wen (PloS one, 2013)
Hippocampal neurons play a critical role in learning and memory; however, the effects of environmental mechanical forces on neurite extension and associated underlying mechanisms are largely unexplored, possibly due to difficulties in maintaining central nervous system neurons. Neuron adhesion, neurite length, and mechanotransduction are mainly influenced by the extracellular matrix (ECM), which is often associated with structural scaffolding. In this study, we investigated the relationship between substrate stiffness and hippocampal neurite outgrowth by controlling the ratios of polydimethylsiloxane (PDMS) base to curing agent to create substrates of varying stiffness. Immunostaining results demonstrated that hippocampal neurons have longer neurite elongation in 35:1 PDMS substrate compared those grown on 15:1 PDMS, indicating that soft substrates provide a more optimal stiffness for hippocampal neurons. Additionally, we discovered that pPKCα expression was higher in the 15:1 and 35:1 PDMS groups than in the poly-L-lysine-coated glass group. However, when we used a fibronectin (FN) coating, we found that pFAKy397 and pFAKy925 expression were higher in glass group than in the 15:1 or 35: 1 PDMS groups, but pPKCα and pERK1/2 expression were higher in the 35:1 PDMS group than in the glass group. These results support the hypothesis that environmental stiffness influences hippocampal neurite outgrowth and underlying signaling pathways.